The carnivore remains from the hominid-bearing Trinchera-Galería, Sierra de Atapuerca, Middle Pleistocene site (Spain) - García García, Nuria; Arsuaga Ferreras, Juan Luis (Geobios, 1998)
Résumé: La faune de carnivores du remplissage à fossiles humains de Trinchera-Galería comprend Cuon alpinuseuropaeus, Canis lupus, Vulpes vulpes, Panthera leo, Lynx pardina spelaea, Felis silvestris, Ursus spelaeus, Meles meles et Mustela sp. Son équivalent actuel se retrouve dans la forêt tempérée de montagne. La rareté inhabituelle des fossiles de hyène pourrait être due à l'homme. La présence de Canis lupus et d'une forme plus ou moins dérivée de lynx indique un âge pléistocène moyen, postérieur au Cromérien. Les restes d'Ursus spelaeus précisent l'âge de cette faune, postérieure à la transition Ursus deningeri/Ursus spelaeus datée de la fin du Pléistocène. Abstract: The carnivore assemblage of the hominid-bearing Trinchera-Galería karst-fill includes Cuon alpinus europaeus, Canis lupus, Vulpes vulpes, Panthera leo, Lynx pardina spelaea, Felis silvestris, Ursus spelaeus, Meles meles and Mustela sp. Modern analogues of this assemblage inhabit temperate montane forest. The unusual scarcity of hyaena remains might be a consequence of the hominid presence. The presence of Canis lupus and a relatively derived lynx, point to a post-Cromerian Middle Pleistocene age. However, the existence of Ursus spelaeus,, limits the age to at least a terminal Middle Pleistocene when the transition from U. deningeri to U. spelaeus is considered to have occurred. Dirección General de Investigación Científica y Técnica (España) Depto. de Geodinámica, Estratigrafía y Paleontología Fac. de Ciencias Geológicas TRUE pub